Application of contrast-enhanced magnetic resonance imaging in the assessment of blood-cerebrospinal fluid barrier integrity. (August 2021) - Verheggen, Inge C.M.; Freeze, Whitney M.; de Jong, Joost J.A.; Jansen, Jacobus F.A.; Postma, Alida A.; van Boxtel, Martin P.J.; Verhey, Frans R.J.; Backes, Walter H.
Highlights: Blood-CSF barrier (BCSFB) function contributes to homeostasis in the interstitium. How BCSFB disruption relates to age-related neurodegeneration is underassessed. Contrast-enhanced MRI can be used to assess BCSFB permeability. Post-contrast gadolinium enhancement in the ventricles can reveal BCSFB disruption. New imaging techniques highly sensitive to CSF are promising for BCSFB assessment. Abstract: VERHEGGEN, I.C.M., W. Freeze, J. de Jong, J. Jansen, A. Postma, M. van Boxtel, F. Verhey and W. Backes. The application of contrast-enhanced MRI in the assessment of blood-cerebrospinal fluid barrier integrity. Choroid plexus epithelial cells form a barrier that enables active, bidirectional exchange between the blood plasma and cerebrospinal fluid (CSF), known as the blood-CSF barrier (BCSFB). Through its involvement in CSF composition, the BCSFB maintains homeostasis in the central nervous system. While the relation between blood-brain barrier disruption, aging and neurodegeneration is extensively studied using contrast-enhanced MRI, applying this technique to investigate BCSFB disruption in age-related neurodegeneration has received little attention. This review provides an overview of the current status of contrast-enhanced MRI to assess BCSFB permeability. Post-contrast ventricular gadolinium enhancement has been used to indicate BCSFB permeability. Moreover, new techniques highly sensitive to low gadolinium concentrations in the CSF, for instance heavily T2-weighted imaging with cerebrospinal fluid suppression, seem promising. Also, attempts are made at using other contrast agents, such as manganese ions or very small superparamagnetic iron oxide particles, that seem to be cleared from the brain at the choroid plexus. Advancing and applying new developments such as these could progress the assessment of BCSFB integrity.